Enhanced ORR catalytic activity of rare earth-doped Gd oxide ions in a CoFe2O4 cathode for low-temperature solid oxide fuel cells (LT-SOFCs). Issue 19 (1st October 2022) - Yousaf, Muhammad; Akbar, Muhammad; Yousaf Shah, M.A.K.; Noor, Asma; Lu, Yuzheng; Akhtar, Majid Niaz; Mushtaq, Naveed; Hu, Enyi; Yan, Senlin; Zhu, Bin
Abstract: The search for cathode materials with fast oxygen reduction reaction (ORR) catalytic activities and high ionic conductivity is the key obstacle to SOFCs commercialization and its operation at low temperatures. In order to search for a cathode with enhanced catalytic functionality, herein we report a single-phase CoFe2 O4 (CFO) and CoGd0.2 Fe1.80 O4 (CGFO), which can be employed as an active cathode to improve electrocatalytic ORR functionalities at low temperature. It is found that CGFO having enriched oxygen vacancies exhibits the least polarization resistance ( R P ) of 0.42 Ωcm 2 compared to the pure CFO which shows polarization resistance of 0.56 Ω cm 2 under H2 /air conditions. Furthermore, Density functional theory (DFT) calculations also show that the number of oxygen vacancies increases in the CGFO sample. The CGFO cathode based SOFC achieved a peak power density (PPD) of 475 mW/cm -2 at 550 °C, higher than CFO cathode based SOFC which delivers 315 mW/cm -2 . Subsequently, fast ORR catalytic functionalities and least electrode polarization resistance make spinel ferrite based CGFO a potential cathode for low-temperature SOFCs.